Effect of Incubation of PK-15 Cell Line with Cryoprotectants on Presence of Gal-alpha-1,3-Gal Epitope - Bohuslavskyi, Kirill I.; Alabedalkarim, Nataliya M.; Pakhomov, Aleksandr B.; Bozhok, Galina A. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):191.